Palynostratigraphy Subang, Kaliwangu, And Citalang Formation, From Cikandung River Passage, Sumedang Regency, West Java - Rizki Satria Rachman; Winantris Winantris (Universitas Diponegoro, 2022)
The Subang, Kaliwangu, and Citalang Formation which are important parts of the Bogor Basin have not been studied, especially from the palynostratigraphic aspect. Therefore, this study aims to conduct palynostratigraphic study of these three formations that are well exposed in the Cikandung River area, Sumedang Regency, West Java. Method used in this research is divided into several stages including sampling by spot sampling; preparation of palynomorphs and palynodebris by hydrogen peroxide and acid methods; identification of samples using CX-22 microscope; analysis and interpretation of data using basic research statistics. Result, the research area was divided into three groups. The first group (sample W.9 – W.10) correlates with the Subang Formation which has predominantly claystone lithology with Middle Miocene age and shallow marine environment. This group is in proximal basin position with dysoxic conditions. The second group (sample W.5 – W.8) correlates with the Kaliwangu Formation which has alternating lithology between sandstone and claystone with younger age than the Middle Miocene and transitional environment. This group is in proximal basin position with dysoxic-anoxic conditions. The third group (sample W.1 – W.4) correlates with the Citalang Formation which has sandstone and conglomerate lithology with younger age than the Middle Miocene (Kaliwangu Formation) and terrestrial environment. This group is in proximal basin position and anoxic conditions. In general, when viewed from palynodebris, the presence of plant material (palynomorph, cuticle, and wood) is negatively correlated with AOM and other rock fragments. On the other hand, in terms of palynomorphs, the presence of foraminifera lining test has negative correlation with other terrestrial palynomorphs, especially those of the Florschuetzia species.